(untitled) (Research, Society and Development, 2021)
The present work aimed to evaluate the physicochemical and biochemical alterations of minimally processed rocket (Eruca sativa Mill). The minimal processing consisted of the steps of selection, standardization, washing, slicing, sanitizing, rinsing and centrifugation. After processing, the minimally processed rocket leaves were placed in plastic packaging of Nylon Poly (NP) and High Density Polyethylene (HDPE) and stored at 5±1°C for a period of 12 (twelve) days. During storage, phenolic compounds, browning index (IE), chlorophyll and carotenoids, soluble solids, total titratable acidity, pH, vitamin C and polyphenol oxidase enzyme activity were evaluated. There was a significant decrease in the contents of Vitamin C, acidity and °Brix, and increase in pH in all treatments, from the 9th day of storage. The arugula leaves conditioned in NP and HDPE also showed an increase in the levels of phenolic compounds and in the activity of the PPO enzyme from the 9th day of storage, which contributed to the increase in the browning index. Thus, it is suggested that for minimum rocket processing, HDPE and NP packages can be used for a storage period of up to nine days.